Analytical and numerical investigations of weld bead shape in plasma arc welding of thin Ti-6al-4v sheets. (December 2017) - Dhinakaran, V; Siva Shanmugam, N; Sankaranarayanasamy, K; Rahul, R
In this research work, a new analytical model has been developed to predict the temperature distribution during plasma arc welding of thin Ti-6Al-4V sheets. Dhinakaran's model based on a three-dimensional parabolic Gaussian heat source is considered as a plasma arc heat source moving on a semi-infinite body to derive the analytical model and the same heat source model is substituted in the three-dimensional Fourier's law of heat conduction and implemented in the finite element package. Thermo physical properties, such as density, specific heat, and thermal conductivity, are used as temperature-dependent properties in finite element simulation. Numerical simulation is carried out using COMSOL. The new analytical model is expressed as a function of three-dimensional spatial co-ordinates and the time co-ordinate. A computer program has been written to solve the analytical model in order to obtain the distribution of transient temperature at any point of interest. The transient temperature distribution predicted by the analytical model has been compared with both the experimental result and the numerical result. Experimental work is carried out to measure the thermal cycle during welding. The thermal cycle is measured by using an infrared thermometer. Very good correlation has been obtained between the predicted transient temperature by analytical solution and the measured temperature, as well as the finite element simulation result. This provides a reliable alternative for using these analytical solutions in the future to obtain the thermal cycle, distortion, and thermal stress during plasma arc welding.